(untitled) (African Journal of Public Administration & Management, 2026)
The APRM was launched on 09 March 2003 by the NEPAD Heads of State and Government What is the APRM? Implementation Committee (HSGIC) in Abuja, Nigeria (NEPAD/HSGIC/03-2003/APRM/MOU (09 March 2003), as a self-monitoring instrument voluntarily acceded to by member states of the African Union. ▪ The APRM is an African-owned and African-led platform for self-assessment, peer-learning, and experience-sharing with the purpose of promoting democratic governance, high economic growth, sustainable development and accelerated regional and continental economic integration. ▪ Since 2017, the AU Assembly has expanded the mission of the APRM to include: i) Tracking the implementation, monitoring and evaluation of Agenda 2063 and SDGs ii) Developing Africa Governance Report every 2 years in collaboration with AGA and APSA iii) Supporting Member States in the field of Credit Rating Agencies. iv) To position the APRM as an early warning tool for conflict prevention on the continent, in the context of harmony and synergy between the APRM, the African Peace and Security Architecture, and the African Governance Architecture